Women heroes of World War II : the Pacific Theater : 15 stories of resistance, rescue, sabotage, and survival - Atwood, Kathryn J. (Chicago Review Press Incorporated, 2016)
Collects the stories of fifteen women who risked their lives to become heroes in the Pacific theater of World War II.